Numerical analysis of parameter identifiability for a mathematical model of a chemical reaction - Nurislamova, L.F.; Gubaydullin, I.M. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2018)
The authors of this paper develop a numerical approach to analyze the parametric identifiability of chemical reaction models by the methods of sensitivity analysis for the efficient study and management of chemical reaction processes. The primary objective of this paper is to determine the parameters to be identified for the propylene pyrolysis process and to determine the insignificant parameters of the model. The 157-step detailed pyrolysis scheme of propane is reduced to the 30-step scheme. A kinetic model is proposed to analyze the low-temperature pyrolysis of propane. This model adequately describes the yield of observed reaction products at atmospheric pressure. The parameters of the kinetic model of propane pyrolysis are identified by solving the inverse problem of chemical kinetics.